Band engineering of high performance p-type FeNbSb based half-Heusler thermoelectric materials for figure of merit zT > 1. Issue 1 (21st November 2014) - Fu, Chenguang; Zhu, Tiejun; Liu, Yintu; Xie, Hanhui; Zhao, Xinbing
Abstract : High performance p-type half-Heusler compounds FeNb1− x Ti x Sb are developed via a band engineering approach and a record zT of 1.1 is achieved. Abstract : We report new p-type FeNb1− x Ti x Sb (0.04 ≤ x ≤ 0.24) half-Heusler thermoelectric materials with a maximum zT of 1.1 at 1100 K, which is twice that of the ZrCoSb half-Heusler alloys. The electrical properties are optimized by a tradeoff between the band effective mass and mobility via a band engineering approach. A high content of Ti up to x = 0.2 optimizes the power factor and reduces the lattice thermal conductivity. In view of abundantly available elements, good stability and high zT, FeNb1− x Ti x Sb alloys could be promising materials for high temperature power generation.